A study of variations in the iron profile and vitamin – b12 levels as predictive bio-chemical markers for gestational diabetes mellitus (gdm) in pregnant women (Funded work) - DR. SHIVA GAUTHAM TEJA SUNKARAPALLI; SUCHITRA KAVURI (International Journal of Pharma and Bio Sciences, 2018)
The prevalence of Gestational Diabetes Mellitus (GDM) is increasing globally and considerably more in developing countries like India.Pertaining to GDM there were some studies suggesting a relationship between iron profiles with impaired Oral Glucose Tolerance Test (OGTT) which is not yet clear. Very few studies are available regarding the relationship of Vitamin-B12 with GDM. The present study was designed to determine the relationship between iron profile and impaired OGTT in pregnant women with GDM and compare this relationship with that of normal pregnant women, along with comparison of Vitamin-B12 levels and also to establish the significance of iron profile and vitamin-B12 levels in the plasma as potent bio-chemical markers for impending GDM.The present study was conducted on 60 pregnant women visiting the OPD of Obstetrics in ASRAMS in 2015. 30 GDM women were included in Test group and 30 normal pregnant women in control group. Serum iron, serum ferritin, Total Iron Binding Capacity-TIBC and vitamin-B12 were estimated and statistical tools like Unpaired Student t-Test and Pearson Correlation Test were employed. Significant increase in levels of serum Iron and serum ferritin was seen in test when compared to controls P < 0.0001. No significant difference was found in TIBC between test and controls P < 0.3. Serum Vitamin-B12 in the test decreased compared to controls P < 0.0001. Increased serum iron and increased serum ferritin correlated positively with increased blood glucose in OGTT, while serum Vitamin-B12 is negatively correlated, inferring their significance as predictive biochemical markers for GDM. Larger comparative studies should be performed to establish this rationale.